The Treasures of Traditional Medicine of Pagar Doa in the Script of Poda ni Alimunan: An Ecolinguistic Study - Latifah Yusri Nasution; Dardanila Dardanila; Dwi Widayati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to describe the lexicon of traditional medicine contained in the Poda ni Alimunan script. The study used a qualitative approach with a descriptive method. The source of research data is the Poda ni Alimunan script. Collecting data by observing method. Data analysis used referential equivalent method and presented using informal method. The results of this study are the traditional treatment of Pagar Doa ‘Doa penjaga’ using the noun lexicon pira manuk na matan gorsing na 'chicken egg with the yolk', porlada 'pepper', lasuna 'garlic', pege tuwak 'ragi', itak poltuk 'gambir'. ', ihan na rata na itutung ' haporas fish that has grilled', tinombu burangir horpit/sorpit lanjang 'betel leaf that meets the segment', sanggu sago mariot 'sanggu bamban', pege tanggul miak baja 'temulawak', Asal Indahan sagata 'one spoon of upa-upa rice', and hayu andulpak 'andulpak wood '. Verb lexicon in Pagar doa, namely the verb dabuwat 'taken'. Patopma 'together', diporso 'served', damintoraima 'mantrailah', morsom 'worship', and paturun Barang balik bali angin hapili 'turns disease back on the owner like a blowing wind'.